CO2 Pipeline Cost Calculations, Based on Different Cost Models - Horánszky, Beáta; Forgács, Péter (Theory, Methodology, Practice – Review of Business and Management, 2013)
Carbon Capture and Storage (CCS) is considered to be a promising technology and an effective tool in the struggle against climate change. The method is based on the separation of air-polluting CO2 from fuel gases and its subsequent storage in different types of geological formations. The outlet points and formations used as CO2 storage sites are often very far from each other. According to certain recently announced, medium-term EU plans, a 20,000 km long pipeline system will be established for the transportation of the gas by 2050, at a cost of 28.5 billion Euros. Obviously, not only technical ad safety planning, but also detailed, itemized financial and investment plans based on cost calculations (including construction and operation costs), are required to make such a grandeus enterprise economically feasible. We reviewed several studies from available literature that use different computational models to determine pipeline construction costs, based on the technical and financial data of natural gas transport pipelines and CO2 pipelines built for Enhanced Oil Recovery (EOR) projects. In the following paper, these cost models are collated and analysed, with regard to their applicability to CCS process planning.